Lipid-based oral formulation in capsules to improve the delivery of poorly water-soluble drugs - Mohite, Popat; Singh, Sudarshan; Pawar, Anil; Sangale, Adinath; Prajapati, Bhupendra G. (Frontiers in Drug Delivery, 2023)
Poorly water-soluble drugs demonstrate significant challenge in pharmaceutical development, which is linked to their limited oral bioavailability and therapeutic efficacy. To overcome these limitations, lipid-based formulations have emerged as a promising approach to enhance the delivery of such drugs. Moreover, encapsulation within capsules to provide a convenient dosage form for oral administration. The encapsulation techniques are optimized to ensure uniform drug content and efficient encapsulation efficiency. Several investigations demonstrated that the lipid-based formulations in capsules significantly improved the solubility and dissolution rate of poorly water-soluble drugs compared to non-lipid formulations. Additionally, the encapsulation of lipid-based formulations protected the drug against degradation and improved its stability. Overall, incorporating lipid-based formulations in capsules represents a promising strategy for enhancing the delivery of poorly water-soluble drugs with improvement in solubility, dissolution, stability, and bioavailability, overcoming the challenges associated with these challenging drug molecules. The review focussed a brief on utilization of lipids in capsule form to improve therapeutic efficacy of poorly soluble, dissolution and bioavailability of drugs.